2016
DOI: 10.1177/0031512516654500
|View full text |Cite
|
Sign up to set email alerts
|

Verbal-Spatial and Visuospatial Coding of the SNARC Effect

Abstract: Using the magnitude comparison task, the current study tested verbal-spatial and visuospatial coding accounts by comparing the spatial-numerical association of response codes effect in 30 Chinese-speaking and 60 bilingual Uighur Chinese participants. The experimental tasks were presented using Chinese words for 30 Chinese-speaking and 30 bilingual Uighur Chinese participants, while only Uighur words were presented to the remaining 30 bilingual Uighur Chinese participants. Overall, the results of the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…RR was also higher from left to right than from right to left ( b = 1.222, SE = 0.090, t = 13.537, p < 0.001). Compared with right to left and LF words, there were shorter fixation durations, higher SP, and lower refixation probability for left to right and HF words, which is consistent with expectations and previous research ( 7 ; 15 ; 12 ; 19 ; 21 ; 22 ; 29 ; 37 ).…”
Section: Experiments 1 Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…RR was also higher from left to right than from right to left ( b = 1.222, SE = 0.090, t = 13.537, p < 0.001). Compared with right to left and LF words, there were shorter fixation durations, higher SP, and lower refixation probability for left to right and HF words, which is consistent with expectations and previous research ( 7 ; 15 ; 12 ; 19 ; 21 ; 22 ; 29 ; 37 ).…”
Section: Experiments 1 Resultssupporting
confidence: 91%
“…In line with criteria from earlier research ( 3 ; 11 ; 12 ; 27 ; 30 ; 35 ; 36 ; 37 ), fixation durations shorter than 80 ms or longer than 800 ms were excluded. We also excluded data if: (1) a participant pressed the key incorrectly during the experiment, resulting in an interruption; (2) data were accidentally lost (e.g., due to head movement); (3) there were fewer than four gazes; or (4) data were outside three standard deviations.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important consideration in the application of these theories to the development of SNAs is the role of plasticity and cognitive flexibility. Behavioral evidence has shown that SNAs not only change over an individual's course of development, but they are also flexible and easily influenced by task demands and task instructions (Georges et al, 2014;Li et al, 2016;Pfister et al, 2013). Such evidence suggests at least some functional flexibility of SNAs, consistent with the view that there is not a single, static MNL.…”
Section: Interactive Specializationmentioning
confidence: 69%
“…Fischer et al, 2003), in early-blind individuals (Crollen et al, 2013), and even when participants are tested on the phonemic content of number words (Fias et al, 1996). The effect is also flexible and can be shaped by task constraints (Georges et al, 2014;Li et al, 2016).…”
Section: Spatial-numerical Associationsmentioning
confidence: 99%